The Cardiovascular Effects of Metformin: Further Reasons to Consider An Old Drug as a Cornerstone in the Therapy of Type 2 Diabetes Mellitus - Anfossi, Giovanni; Russo, Isabella; Bonomo, Katia; Trovati, Mariella (Current Vascular Pharmacology, 2010)
Cardiovascular events occurring in type 2 diabetes (T2DM) are a major problem in clinical practice. In particular, the risk of myocardial infarction (MI) presented by patients affected by T2DM without previous cardiac events is similar to that of non-diabetic patients with previous MI. To reduce the elevated cardiovascular risk associated with T2DM, tight glycemic control and aggressive therapy against all known cardiovascular risk factors are strictly required. Despite the role played by hyperglycemia in the pathogenesis of cardiovascular events, studies showing an improvement of cardiovascular outcomes by anti-hyperglycemic or hypoglycemic agents are not conclusive. The United Kingdom Prospective Diabetes Study (UKPDS) demonstrated that in obese type 2 diabetic patients metformin reduces the risk of MI more than sulphonylureas or insulin. This observation identified metformin as the first-line treatment for T2DM. The vasoprotective role of metformin is largely independent of its hypoglycemic action and has been ascribed to pleiotropic effects. The present review considers the putative beneficial action exerted by metformin on arterial vessels by evaluating its effects on lipids, inflammation, hemostasis, endothelial and platelet function and vessel wall abnormalities. Furthermore, the molecular mechanisms of the beneficial metabolic and vascular effects of metformin will be considered, with a particular attention for its ability to activate AMP-activated protein kinase.
Keywords: oxidative stress